Structural dynamics of innovation networks in German leading-edge clusters - Uwe Cantner; Holger Graf; Stefan Töpfer (Friedrich Schiller University Jena, 2015)
We study the effects of a German national cluster policy on the structure of collaboration networks. The empirical analysis is based on original data that was collected in fall 2011 and late summer 2013 with cluster actors (firms and public research organizations) who received government funding. Our results show that over time the program was effective in initiating new cooperation between cluster actors and in intensifying existing linkages. Newly formed linkages are to a substantial amount among actors who did not receive direct funding for a joint R&D project, which indicates an additional, mobilisation effect of the policy. Furthermore, we observe differential developments regarding clusters spatial embeddedness. Some clusters tend to increase their localisation, whereas others increase their connectivity to international partners. The centrality of large firms increased over time, indicating their prominent role as preferred partners for R&D cooperation within the clusters while it is the opposite case for public actors.
Keywords: O38; L14; R10; 330; cluster; innovation policy; evaluation; social network analysis